Barnard's Syndrome: Biliary Ileus Secondary to Bilioenteric Fistula. Case Report - Garcia Felix, Itzel Guadalupe; Grande Ramirez, Cesar Ivan; Lozano Lugo, Leonel; Torres Ordaz, David Eduardo (International Journal of Medical Science and Clinical Research Studies, 2025)
Biliary ileus is a rare cause of intestinal obstruction, first described by Bartholin in 1654, is an impaction of gallstones into the intestinal tract through a cholecystoenteric fistula (CEF). A CEF, a relatively rare complication of gallstones, is defined as an autonomous communication between the inflamed gallbladder and the surrounding adherent gastrointestinal tract, usually secondary to Mirizzi's syndrome. Computed tomography (CT), with a sensitivity greater than 90% and specificity close to 100%. The treatment of biliary ileus is surgical and is mainly aimed at resolving the intestinal obstruction, the optimal surgical approach is still under debate. There are mainly 3 current surgical options: isolated enterotomy with spontaneous closure of the fistula, one-stage surgery performing enterolithotomy with cholecystectomy and closure of the fistula, and lastly two-stage surgery consisting of enterolithotomy followed by cholecystectomy and closure of the fistula.